ON UNDERSTANDING OF PHILOSOPHY: HISTORICAL AND PHILOSOPHICAL DISCUSSIONS OF THE XX – XXI CENTURIES - Sukhodub, Tetiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The article discusses the features of «classical» and modern philosophy, types of philosophical and social thinking as a subject of modern philosophical discourse. The aim of the study is to analyze the culture of «classical» and modern philosophical thinking in the context of their positive and negative aspects, as well as the impact on the social and cultural development of modern humanity. Research tasks are to analyze the features and basic principles of «classical» and «modern» philosophical thinking as types of philosophizing; to show the inexpediency of a one-sided approach to the classical tradition as an «utopian project». The core of the research methodology is based on historical and philosophical, scientific and systemic, comparative approaches. The analysis also applied the methodology of the hermeneutics of consciousness. Research results. Utopian thinking as a variant of «social project» passes through all cultural and historical eras, therefore there is no reason to associate it exclusively with the «philosophy of modern». A critical analysis of the philosophy of the XIX century in modern discourse allows us to assert that the category of «universal», with which this tradition works, is a «classical» way of philosophical categorical and logical thinking about the foundations of a person’s social and cultural existence and allows one to reason problematic, but not utopian. Discussion. The works of domestic and foreign researchers, which considered the problem of understanding philosophy as a certain culture of thinking were of scientific interest. In particular, there were of A. Badiou, V. Zagorodniuk, P. Kozlowski, S. Kutsepal, V. Hösle, A. Vogt, M. Heidegger, E. Shatsky and others. Conclusions. The history of philosophizing in the XX and the first decades of the XXI century shows a hidden or explicit state of debatability between two types of philosophical thinking – «classical» and «modern» (post-classical). Moreover, the modern type (in its most diverse directions) is aimed at deconstructing the «classical» version of thinking. Rejection primarily causes utopianism as a «general project» for the transformation of reality. However, utopianism, irrational social «projecting» does not belong to «classical» philosophical thinking and are not its essential feature. The phenomenon of utopia as a type of social thinking is characterized by cultural transhistoricity and a paradoxical combination of the principles of anti-historicism and progressivism.